Inovasi Biskuit Jagung-Teri untuk Pengentasan Stunting di Desa Oebobo, Timor Tengah Selatan - Elok Waziiroh; Susinggih Wijana; Atiek Iryani; Nurul Muslihah; Delphi Putri Atdinata; Fathiya Zahra Afia; Lufita Shela Ardini; ⁠Tengku Reza Sofiyati; Tyolina Maryam Gultom (Institut Pertanian Bogor, 2026)
Oebobo Subdistrict, South Central Timor Regency, East Nusa Tenggara, Oebobo Village has considerable potential for maize production. However, despite the abundance of this local resource, the prevalence of stunting among children under five remains high, reaching 51.94% (BPS TTS, 2023). This community empowerment program was designed to enhance local capacity in utilizing maize as a nutritious food source through the production of fortified biscuits enriched with anchovy flour as a protein source. The program aimed to improve community skills in processing locally available agricultural products into nutrient-dense foods that support stunting prevention while promoting food diversification and local economic development. The program was implemented through educational socialization, hands-on training using a learning-by-doing approach, and practical skill evaluations. Participants included integrated health service post (Posyandu) cadres, pregnant women, and members of the Binonmeto farmer and micro-enterprise group. The results demonstrated a substantial improvement in participants’ technical skills in maize biscuit production, with more than 80% successfully completing the practical assessment. Furthermore, the developed biscuits were well accepted by the community, achieving a hedonic preference score of 4.3 out of 5. The expected outcomes of this program include enhanced nutritional knowledge, increased utilization of local maize-based food products, strengthened community capacity in producing nutritious foods, and improved economic opportunities through value-added processing of local agricultural commodities. The program contributes to supporting community-based strategies for stunting reduction and sustainable local food development.